Revisiting inclusion in smart cities: infrastructural hybridization and the institutionalization of citizen participation in Bengaluru's peripheries. (1st January 2023) - van Gils, Bart A. M.; Bailey, Ajay
ABSTRACT: Smart city development can be traced back in the urban development trajectories of cities, as well as the respective articulations, framing and practices of 'inclusive' and 'participatory' smart cities. As smart city development steadily gains more and more traction among urban policy makers throughout the Global South, many scholars warn for its negative consequences on the accessibility of infrastructure and the processes that transform democratic citizenship practices. Rather than perceiving the transformative power of smart cities as a phenomenon particular to the use of new technologies, this paper aims to analyse societal segregation and marginalization through smart city development and traces these externalities as a continuation or intensification of existing governance practices. This is demonstrated by the case study on the metropolitan city of Bengaluru, that participates in India's national Smart City Mission. Due to massive urbanization, Bengaluru's peripheries are suffering from increasing pressures on its basic infrastructure. In response, state actors have turned to hybridizing the city's infrastructure facilities and governance to market- and civil society actors. Furthermore, the efforts of middle-class civil society groups that contribute to infrastructural governance through the assistance in planning, facilitation and controlling state responsibilities are institutionalized by bureaucratic state actors, at the cost of electoral governance by local representatives. This analysis on infrastructure governance in the peripheries has been set in relation to a discourse analysis of official policy documents on the inclusive and participatory character of smart cities. The practices of hybridization and institutionalization not only undermine the access to basic infrastructure for marginalized groups but also heavily underpin the design of Bengaluru's smart city projects. To be called inclusive, we argue that smart city projects should make an effort to improve the overall accessibilities of infrastructures for all classes and population groups.